Increasing Maru Design’s Brand Awareness by Making a Promotional Video - Amerine Tabita (Kata Kita: Journal of Language, Literature, and Teaching, 2022)
Maru Design's main target market is start-up businesses and small to medium business owners, ranging between 20 to 30 years old. Due to COVID-19, Maru Design had a problem managing and dividing the team because the company lacked workforce. Consequently, Maru Design’s Instagram and YouTube page tended to be inactive. As a result, Maru Design was experiencing low brand awareness problem. I conducted an online questionnaire to 102 people who were representatives of Maru Design’s target market, which was Surabaya citizens between the ages of 20 and 40. The solution was creating a promotional video in partnership with Maru Design. This promotional video can be used to increase the brand awareness of Maru Design by showing the unique selling point (USP) of the company. The promotional video was made by applying theories in the steps of making a promotional video (Maguire, 2016) and language used (Samantha, 2014). This video is aimed at improving the company’s brand awareness for future clients. Keywords: Brand Awareness, Promotional Video, Branding